Ekstraksi Gelatin dari Tulang Ikan Tongkol (Euthynnus affinis) dengan Menggunakan Asam Belimbing Wuluh (Averrhoa bilimbi L): Gelatin Extraction from Tongkol Fish Bone (Euthynnus affinis) using Acid from Starfruit (Averrhoa bilimbi L) - Musafira Musafira; Sulistiawati; Rismawati Sikanna (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2023)
Gelatin is a type of protein resulting from the partial hydrolysis of collagen found in animals' skin, bones, and connective tissue. Gelatin is widely used in the food and pharmaceutical industries. Using Tongkol fish bones as a source of gelatin is a safe alternative for the human body and halal for consumption. Characteristics of gelatin from the bone waste of Tongkol fish extracted with starfruit acid are important to know, therefore it can be used as a substitute for cow and pork skin. The purpose of this study was to determine the characteristics of Tongkol fish bone gelatin extracted with tamarind starfruit. The extraction method was used in this research using 5 levels of starfruit acid concentration (10%, 20%, 30%, 40%, 50%) with the ratio of solvent and fish bones 1: 4 (w/v). The use of starfruit acid with a concentration of 40% produced the highest yield with the characteristics of the resulting gelatin having a brownish yellow color, yield of 1.43%, water content of 17%, ash content of 15%, degree of acidity (pH) of 6.5 and protein content of 47.98%.